2021
DOI: 10.1126/sciadv.abi8584
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive hybridization with local wild relatives in Western European grapevine varieties

Abstract: Hybridization footprint suggests introgression with local wild relatives in Western European grape varieties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 90 publications
4
24
0
Order By: Relevance
“…Previous studies showed that the genetic basis of crops was produced through domestication events followed by adaptive gene flow from relatives encountered during postdomestication expansion processes ( Janzen et al 2019 ). New genomic data reveal that introgressed loci of large effect that are target of directional selection explain a small proportion of the full phenotypic variance in traits associated with altitudinal, latitudinal, and longitudinal climatic gradients in different crop species (phenotypic variance associated with cold stress [maize; Crow et al 2020 ], drought stress [wheat, grapevine, and ryegrass; He et al 2019 ; Blanco-Pastor et al 2021 ; Freitas et al 2021 ] and day length [potato] differences [ Hardigan et al 2017 ]). These studies also show that the evolutionary consequences of introgression from wild relatives are also far more diverse than previously identified ( Martin and Jiggins 2017 ; Warburton et al 2017 ; Suarez-Gonzalez, Lexer, et al 2018 ; Janzen et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that the genetic basis of crops was produced through domestication events followed by adaptive gene flow from relatives encountered during postdomestication expansion processes ( Janzen et al 2019 ). New genomic data reveal that introgressed loci of large effect that are target of directional selection explain a small proportion of the full phenotypic variance in traits associated with altitudinal, latitudinal, and longitudinal climatic gradients in different crop species (phenotypic variance associated with cold stress [maize; Crow et al 2020 ], drought stress [wheat, grapevine, and ryegrass; He et al 2019 ; Blanco-Pastor et al 2021 ; Freitas et al 2021 ] and day length [potato] differences [ Hardigan et al 2017 ]). These studies also show that the evolutionary consequences of introgression from wild relatives are also far more diverse than previously identified ( Martin and Jiggins 2017 ; Warburton et al 2017 ; Suarez-Gonzalez, Lexer, et al 2018 ; Janzen et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental adaptation played a key role in both the evolution of wild genotypes and the outcome of introgression with cultivated varieties. Freitas et al (2021) found significantly enriched climate- and pathogenesis-associated loci in introgressed genomic regions of Iberian cultivated grapevines. The proportion of introgressed regions ranged from 25% to 50% of the grapevine genome, in a set of related Iberian varieties.…”
Section: Grapevinementioning
confidence: 91%
See 3 more Smart Citations